2013
DOI: 10.1186/1129-2377-14-26
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal hemicrania: a retrospective study of a consecutive series of 22 patients and a critical analysis of the diagnostic criteria

Abstract: Background: Paroxysmal hemicrania (PH) is a probably underreported primary headache disorder. It is characterized by repeated attacks of severe, strictly unilateral pain lasting 2 to 30 minutes localized to orbital, supraorbital, and temporal areas accompanied by ipsilateral autonomic features. The hallmark of PH is the absolute cessation of the headache with indomethacin. However, these all features may not be present in all cases and a few cases may remain unclassified according to the 2nd Edition of The Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…PH is typically characterized by repeated attacks of severe, strictly unilateral pain lasting 2–30 min, localized to orbital, supraorbital, and temporal areas accompanied by ipsilateral autonomic features of conjunctival, nasal, facial and eyelid symptoms or signs. But some atypical PH patients do not have accompaniment of autonomic symptoms and the pain duration may extend to hours (Boes and Dodick 2002 ; Maggioni 2010 ; Prakash et al 2013 ). This atypical episodic or chronic PH may have some LH-like features, but the LH pain striding the trigeminal and occopital nerve innervating areas is obviously different from the PH pain localized to orbital, supraorbital, and temporal areas or in any combination of these sites.…”
Section: Discussionmentioning
confidence: 99%
“…PH is typically characterized by repeated attacks of severe, strictly unilateral pain lasting 2–30 min, localized to orbital, supraorbital, and temporal areas accompanied by ipsilateral autonomic features of conjunctival, nasal, facial and eyelid symptoms or signs. But some atypical PH patients do not have accompaniment of autonomic symptoms and the pain duration may extend to hours (Boes and Dodick 2002 ; Maggioni 2010 ; Prakash et al 2013 ). This atypical episodic or chronic PH may have some LH-like features, but the LH pain striding the trigeminal and occopital nerve innervating areas is obviously different from the PH pain localized to orbital, supraorbital, and temporal areas or in any combination of these sites.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] A more recent prospective study of 31 patients found a female to male ratio of 1:1[ 7 ] similar to a smaller retrospective cohort of 22 patients. [ 8 ] This is in contrast to cluster headache which is about three times as common in men. [ 9 10 ]…”
Section: S Ex D Istributionmentioning
confidence: 99%
“…The median dose was 175 mg/day . In Prakash et al's series of PH patients, the mean effective daily dose of IMC was 149 mg (range 50–225) …”
Section: Imc Pharmacologymentioning
confidence: 99%
“…In the Prakash et al paper, 23 patients showed complete response to IMC within 24 hours. It took more than one week for 12% of the patients to achieve remission . In the Pareja et al series, the patients took “approximately 3 days” to respond to their IMC treatment …”
Section: Imc Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation